Bioplastics and their thermoplastic blends from Spirulina and Chlorella microalgae. Issue 5 (14th June 2013) - Zeller, Mark Ashton; Hunt, Ryan; Jones, Alexander; Sharma, Suraj
ABSTRACT This research study focuses on the thermomechanical polymerization of microalgae protein biomass such as Chlorella and Spirulina to develop algal‐based bioplastics and thermoplastic blends. The algal protein biomass can grow on nutrient‐rich wastewater from livestock farms, municipal or industrial effluent sources, remediating the excess nitrogen and phosphorus. The algal bioplastics provide biodegradability that can be tailored to have a wide range of material properties suitable for various applications—consumable and disposable plastic products, agricultural plastic products, and horticultural planting containers. According to experimental results, pressure, temperature, content of plasticizer, and processing time are major variables in polymerization and structure stabilization during the compression molding process of both algal protein biomass and thermoplastic blends containing polyethylene polymer. Chlorella showed better bioplastic behavior than Spirulina microalgae, whereas Spirulina showed better blend performance. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 3263–3275, 2013